2010
DOI: 10.5005/jcdp-11-2-49
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness Level of Oral Cancer in a Group of Dental Patients

Abstract: Aim:The aim of this study was to evaluate levels of public awareness and knowledge about early signs and risk factors of oral cancer among a group of dental patients in Turkey. Methods and Materials:This study included 1022 participants. Sociodemographic information of patients was obtained. A questionnaire about awareness and knowledge of oral cancer and early signs and risk factors related to the disease was completed by two examiners. Data were statistically analyzed with descriptive analyses, crosstabs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
4
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
5
14
4
6
Order By: Relevance
“…This could be because of lack of adequate information given to the public, also not everyone may feel it necessary to gain knowledge about oral cancer. This finding is consistent with the reports of the study by Elango et al (2009) (Pakfetrat et al, 2010) and Peker and Alkurt (Turkey) (Peker and Alkurt, 2010).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…This could be because of lack of adequate information given to the public, also not everyone may feel it necessary to gain knowledge about oral cancer. This finding is consistent with the reports of the study by Elango et al (2009) (Pakfetrat et al, 2010) and Peker and Alkurt (Turkey) (Peker and Alkurt, 2010).…”
Section: Discussionsupporting
confidence: 95%
“…These results were considerably higher compared to our result with 18.3%. In our study, knowledge about early signs of oral cancer was remarkably low with 4.8% compared to studies using patients' samples among Italians (Villa et al, 2011), Turkish (Peker and Alkurt, 2010) and Iranian (Pakfetrat et al, 2010) with a wide knowledge range of 9e79%. In the public samples (Tomar and Logan, 2005;West et al, 2006;Hertrampf et al, 2011a, Hertrampf et al, 2011b, a knowledge range was observed from 26% to 50%.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Only 532 participants (53.2%) were aware of oral cancer; the remaining participants had never heard of oral cancer. Oral cancer awareness found in the present study was slightly higher than a previous study conducted in Turkey in 2010 . However, our results are similar to previous studies from other parts of the world that ranged from 56% to 96% .…”
Section: Discussionsupporting
confidence: 80%
“…Good public awareness of oral cancer would increase the number of patients reporting with early signs to primary care centers, therefore increasing the possibility of early detection . While there are many studies that have reported oral cancer knowledge of people from different countries, studies from Indonesia are lacking . Therefore, the aim of this present study was to investigate the awareness of oral cancer among adults in Jakarta and to determine the factors influencing oral cancer awareness.…”
Section: Introductionmentioning
confidence: 96%